Internet Retailing as a Marketing Strategy - Maarten C.W. Janssen; Rob van der Noll (Tinbergen Institute, 2005)
We analyze the incentives for incumbent bricks-and-mortar firms and newentrants to start an online retail channel in a differentiated goods market. Tothis end we set up a two-stage model where firms first decide whether or notto build the infrastructure necessary to start an online retail channel and thencompete in prices using the channels they have opened up. Consumers trade-offthe convenience of online shopping and the ease to compare prices, with onlineuncertainties. Without a threat of entry by a third pure online player we findthat for most parameter constellations firms' dominant strategy is not to openan online retail channel as this cannibalizes too much on their conventionalsales. As the cannibalization effect is not present for a pure Internet player,we show that these firms will start online retail channels under a much widerrange of parameter constellations. The threat of entry may force incumbentbricks-and-mortar firms to deter entry by starting up an Internet retail channelthemselves. We also show that a low cost of building up an online retail channelor online shopping conveniences may not be to the benefit of online shoppingas the strategic interaction between firms may be such that no online retailchannel is built when the circumstances seem to be more favourable.
Keywords: D43; I13; M30; 330; E-Commerce; Internet; multichannel competition; online uncertainty; online shopping convenience; E-Business; Einzelhandel; Vertriebsweg